The Effectiveness Of Pilates Exercises On Sitting And Standing Balance In Children With Cerebral Palsy - Suharto Suharto; Sri Saadiyah Leksonowati; Tiar Erawan; Arpandjam'an Arpandjam'an (CV. Inara, 2023)
The main problem of this research is the balance disorder of sitting andstanding in children with cerebral palsy. This disorder occurs because ofbrain damage during the non-progressive growth and development ofchildren, thus limiting the daily activities of children with cerebral palsy.The purpose of this study was to evaluate the effectiveness of the Pilatesexercises method on sitting and standing balance in children with cerebralpalsy. This type of research is an experiment with a pre test – post test onegroup design which was carried out for a period of 16 weeks. The researchsubjects were children with cerebral palsy who met the inclusion criteria asmany as 33 people. The study was carried out at the Education Foundationfor Children with Disabilities in Makassar, South Sulawesi, Indonesia and ata children's physiotherapy clinic in Makassar, from February to July 2022.The results of the Paired t test statistical test obtained p value = 0.002 forsitting balance and for standing balance p = 0.002 0.083 which means thereis no difference in standing balance before and after giving Pilatesexercises.